The Homebrewed Christianity Guide to Church History : Flaming Heretics and Heavy Drinkers - Leonard, Bill (Bill J.) (Homebrewed Christianity guide., 2017)
Amid the ferment of dissent and the protests of heretics, the church developed most significantly. This guide introduces that history by looking at those periods. A variety of questions have preoccupied Christian communities throughout history. Christians have attempted to determine who Jesus is and whether his life and teaching have global significance. They've battled over the nature of salvation and the sources of authority for Christian belief and practice. They've argued about the nature and purpose of the Christian church and how is it to be organized. They've drawn swords over the relationship between church and state. And they've taken votes on who should be sainted and who should be expelled. Focusing on sources of unity and division within the church throughout its history, and some of the most and least savory characters in the history, this guide provides an overview of Christian responses to those and other formative questions, all with the trademark Homebrewed Christianity wit and wisdom.